Can simvastatin reduce COPD exacerbations? A randomised double-blind controlled study. Issue 1 (29th July 2021) - Schenk, Peter; Spiel, Alexander O.; Hüttinger, Felix; Gmeiner, Micheline; Fugger, Josefine; Pichler, Martina; Pichler, Gernot; Schmeikal, Susanne; Janistyn, Wolfgang; Schügerl, Stefan; Sajdik, Constantin; Herkner, Harald
Background: Several studies have shown that statins have beneficial effects in COPD regarding lung function decline, rates and severity of exacerbation, hospitalisation and need for mechanical ventilation. Methods: We performed a randomised double-blind placebo-controlled single-centre trial of simvastatin at a daily dose of 40 mg versus placebo in patients with Global Initiative for Chronic Obstructive Lung Disease criteria grades 2–4 at a tertiary care pulmonology department in Austria. Scheduled treatment duration was 12 months and the main outcome parameter was time to first exacerbation. Results: Overall, 209 patients were enrolled. In the 105 patients taking simvastatin, time to first exacerbation was significantly longer compared to the 104 patients taking placebo: median 341 versus 140 days (log-rank test p<0.001). Hazard ratio for risk of first exacerbation for the simvastatin group was 0.51 (95% CI 0.34–0.75; p=0.001). Rate of exacerbations was significantly lower with simvastatin: 103 (41%) versus 147 (59%) (p=0.003). The annualised exacerbation rate was 1.45 events per patient-year in the simvastatin group and 1.9 events per patient-year in the placebo group (incidence rate ratio 0.77, 95% CI 0.60–0.99). We found no effect on quality of life, lung function, 6-min walk test and high-sensitivity C-reactive protein. More patients dropped out in the simvastatin group compared to the placebo group (39 versus 29). Conclusion: In our single-centre RCT, simvastatin at a dose of 40 mg daily significantly prolonged time to first COPD exacerbation and reduced exacerbation rate. Acute exacerbations of COPD cause a lot of suffering and healthcare burden. In this study, p.o. simvastatin 40 mg·day −1 reduced time to first exacerbation and exacerbation frequency in a double-blind, randomised controlled trial. https://bit.ly/3nHINet